Diabetes control, dyslipidemia, hsCRP and mild cognitive impairment in non-elderly people with type 2 diabetes mellitus - Kumar, Naveen; Singh, Veer Bahadur; Meena, Babu Lal; Kumar, Deepak; Kumar, Harish; Tiwari, Arun (International Journal of Research in Medical Sciences, 2019)
Background: Mild Cognitive Impairment (MCI) a transitional stage between normal aging and dementia has been observed more in people with diabetes when compared with general population. The risk factors for MCI in type 2 diabetes mellitus (T2DM) have been defined in elderly patients and aging may itself contribute to declining in cognitive functions. As the large number people with T2DM are under 60years, the prevalence of MCI and factors contributing to it are not much studied. So, this study aimed to find out the factors contributing to MCI in non-elderly T2DM patients. Methods: In this cross-sectional study, 257 patients with T2DM underwent cognitive assessment by Montreal cognitive assessment test and the cognitive levels were correlated with their glycosylated hemoglobin, lipid profile, and highly sensitive C-reactive protein (hsCRP). Results: The prevalence of mild cognitive impairment (MCI) was 64.2%. MCI significantly correlated with duration of diabetes, socioeconomic status, HbA1c, serum triglycerides, low-density lipoprotein, very low-density lipoprotein and hsCRP levels. The factors that were statistically insignificant were body mass index and high-density lipoprotein levels. Conclusions: Cognitive impairment is seen even in non-elderly T2DM patients. It should be considered along with the other complications of diabetes and individuals with T2DM should be screened for cognitive impairment to prevent progression to dementia.